EFFICACY OF DEODARVYADI CHURNA WITH ARAND OIL IN LUMBAR SPONDYLOSIS - Damle D Neena; Archana P Gharote (International Journal of Applied Ayurved Research, 2017)
Osteoarthritis of the cervical and lumbar spine is referred to as spondylosis. Lumbar Spondylosis is a chronic,progressive, skeletal degenerative disease which is common in elderly.In this study total 10 patients suffering from Lumbar Spondylosis were selected. Deodarvyadi churna 3gm BD with Arand oil 5ml was given with warm water twice a day before food for 2 months duration. Pain and function assessment done by Western Ontario and McMaster Universities OA index (WOMAC scale) and VAS (Visual analog Scale) Scale pre-study and at every monthly visit at D.Y. Patil School of Ayurved and Research Institute, Nerul, Navi Mumbai. The Statistical Analysis was done by Wilcoxon matched pairs signed rank test. Patients showed improvement gradually in back pain on WOMAC, VAS scales and average weight reduction up to 2kg was also noticed after 8 weeks. Patients of Lumbar Spondylosis improved at level of significance p<0.0001 for WOMAC scale and weight & p<0.0002 for VAS scale. Deodarvyadi churna improve overall digestion (Aampachan) of patient due to its penetrating hot properties (ushna tikshna guna,katu rasa ,ushna virya and katu vipaka).Aranda oil is doing amapachan and vatanuloman and relieving pain associated with lumbar Spondylosis .According to Ayurveda margavarodhajanya Katigatavata patients showed improvement with Deodarvyadi Churna with Aranda Oil. So Devadarvyadi Churna with Aranda Oil is significantly useful in relieving symptoms and improving movements of patients of Lumbar Spondylosis.